IgY antibodies: The promising potential to overcome antibiotic resistance - El-Kafrawy, Sherif A.; Abbas, Aymn T.; Oelkrug, Christopher; Tahoon, Marwa; Ezzat, Sameera; Zumla, Alimuddin; Azhar, Esam I. (Frontiers in Immunology, 2023)
Antibiotic resistant bacteria are a growing threat to global health security. Whilst the emergence of antimicrobial resistance (AMR) is a natural phenomenon, it is also driven by antibiotic exposure in health care, agriculture, and the environment. Antibiotic pressure and inappropriate use of antibiotics are important factors which drive resistance. Apart from their use to treat bacterial infections in humans, antibiotics also play an important role in animal husbandry. With limited antibiotic options, alternate strategies are required to overcome AMR. Passive immunization through oral, nasal and topical administration of egg yolk-derived IgY antibodies from immunized chickens were recently shown to be effective for treating bacterial infections in animals and humans. Immunization of chickens with specific antigens offers the possibility of creating specific antibodies targeting a wide range of antibiotic-resistant bacteria. In this review, we describe the growing global problem of antimicrobial resistance and highlight the promising potential of the use of egg yolk IgY antibodies for the treatment of bacterial infections, particularly those listed in the World Health Organization priority list.